2006
DOI: 10.1002/nml.120
|View full text |Cite
|
Sign up to set email alerts
|

Historical research for the nonprofit sector

Abstract: Because there are many possible uses of history and conceptions of what constitutes historical inquiry, there can be no single description of “historical research for the nonprofit sector.” Nonprofit researchers, like all nonprofit leaders, cannot avoid having views of historical development; neither can they avoid the necessity of drawing conclusions from incomplete and indeterminate evidence, just as all historians must do. Students of the Nonprofit sector might want to pay particular attention to questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…This paper contends that it is time to speed up this development and install history as a major feature of non-profit education, drawing on an earlier pioneering study by Hammack (2006). It argues that the study of history can add significantly to nonprofit education; respectively suggesting that no serious non-profit studies course can ignore an historical dimension.…”
Section: Introductionmentioning
confidence: 95%
“…This paper contends that it is time to speed up this development and install history as a major feature of non-profit education, drawing on an earlier pioneering study by Hammack (2006). It argues that the study of history can add significantly to nonprofit education; respectively suggesting that no serious non-profit studies course can ignore an historical dimension.…”
Section: Introductionmentioning
confidence: 95%
“…The increased competition for revenues has led the nonprofits to act more business‐like with commercial activities, venturing into services previously considered government and private sector's territory, and, driving more revenues from sale of services (Bromley & Meyer, ; Dees & Anderson, ; Hammack, ; Levine Daniel & Galasso, ). Brandsen, Van de Donk, and Putters () suggested that nonprofit sector in its current state seems to be something other than community, state, and market (Knutsen, ) with continuous collaboration within and outside sector with businesses and governments (Ihm & Shumate, ) causing complexity (Kendall & Knapp, ; Maier, Meyer, & Steinbereithner, ; S. R. Smith, ), mission drift (Doherty, Haugh, & Lyon, ; Levine Daniel & Galasso, ; Maier et al, ), and, often leading them away from their traditional identities (Binder, ).…”
Section: Organizational Identity and The Non‐profit Sectormentioning
confidence: 99%
“…An unintended consequence of this devolution in government authority, uncovered by Hamann and Foster (), is that employees of not‐for‐profit agencies report experiencing higher work demands than their public and for‐profit counterparts. As the percentage of public sector goods and/or services contracted out grows (Boris, de Leon, Roeger, & Nikolova, ; Hammack, ) and the need for these services continues to expand (Ronquillo et al, ), their finding suggests that work demands' detrimental employee‐related effects will become increasingly problematic for not‐for‐profit human service agencies. Consequently, empirical research that investigates and identifies organizational factors capable of buffering work demands' strain‐inducing impact not only helps not‐for‐profit human service employees, but may also improve their agency's performance.…”
Section: Introductionmentioning
confidence: 99%